ROOT CAUSE ANALYSIS: SOLID WASTE MANAGEMENT (CASE STUDY ON MARKET) (Proceedings of the International Conference on Public Health, 2023)
Waste production in Indonesia increase year by year, which come from various waste production resource and one of them is market which until now still poorly handled. Based on the previous study, there are several problems related with the flow of waste management. Therefore, this study aims to identify the root of the problem of the solid waste management in the market. This study uses a type of qualitative research and data were analyze with fishbone diagram which was categorizing problem based on four aspects, consist of organizational aspects, technical aspects, environmental aspects, and sociocultural aspects. The results showed that environmental aspect appeared as a main problem in the market with zero implementation of Integrated of Solid Waste Management indicator which consist of residual waste handling, waste management program, and number of recycle bins. In conclusion, to solve the environmental-related problem, there should be knowledge and capacity training about waste management for all the stakeholders. Apart of that, stakeholder analysis is needed to ensure all of the market’s stakeholders can develop a plan and strategy for managing solid waste.
Keywords: fishbone diagram; solid waste; market; problem analysis